Nanosponges – A Review on Noval Drug Carriers - A, Anto.; kumar.S, Ranjith; L.V, Vigneshwaran; Kumar.M, Senthil (Journal of Biomedical and Pharmaceutical Research, 2022)
Pharmaceutical nanotechnology, the pharmaceutical sciences’ most recent subfield, offers new resources, chances, and possibilities that are anticipated to have a big impact on illness treatment and diagnosis.. Pharmaceutical nanotechnology comprised of nano-sized products which can be transformed in numerous ways to improve their characteristics. A Nanosponge is a novel and emerging technology which offers targeted & controlled drug delivery for topical as well as oral use. Nanosponges are based on nano, polymer-based spheres that can suspend or entrap a wide variety of substances and then be incorporated into a formulated product such as a gel, lotions,cream, ointments, liquid or powder. This technology offers entrapment of ingredients and thus reduced side effects, improved stability, increases elegance and enhanced formulation flexibility.A component of advanced medicine delivery is nanosponge. It is a special tool for the regulated administration of both lipophilic and hydrophilic medicines to specific patient populations. Keyword: Nanosponges, Cyclodextrins,Drug delivery